Benign Neonatal Sleep Myoclonus Evokes Somatosensory Responses. Issue 6 (November 2017) - Losito, Emma; Eisermann, Monika; Vignolo, Patricia; Hovhannisyan, Shushanik; Magny, Jean François; Kaminska, Anna
Abstract : Purpose: Benign neonatal sleep myoclonus is a common nonepileptic condition occurring in neurologically normal full-term newborns. During jerks, EEG has always been described as normal. The aim of this study was to describe EEG changes associated with the myoclonic jerks. Methods: Polygraphic video-EEG recordings of four full-term neonates presenting benign neonatal sleep myoclonus were studied. Myoclonic jerks were analyzed regarding their topography, frequency, propagation pattern, and reflex component. EEG averaging time-locked to myoclonic jerks and to somatosensory stimuli (realized by tapping on palms and feet) was performed to study eventual EEG correlates of myoclonus and to asses somatosensory evoked responses—for the latter, two control newborns were added. Results: Visual analysis of the EEG disclosed theta band slow waves on central and vertex electrodes concomitant to myoclonic jerks and jerk-locked back-averaging disclosed a sequence of deflections, not preceding, but following the myoclonus. This response predominated on the vertex electrode (CZ) and consisted of five components (N1, P1, N2, P2, and N3), with only the three later components being constantly present (at 110, 200, and 350–500 ms, respectively). Back-averaging locked to the tactile stimuli in four subjects and two control newborns showed similar components and were comparable to those described in the literature as late somatosensory evoked responses in full-term newborns. Conclusions: Myoclonic jerks in benign neonatal sleep myoclonus can evoke visually identifiable EEG potentials on vertex electrodes corresponding to somatosensory responses. This EEG aspect may be misleading and could give rise to an anti-seizure treatment that mostly worsens the condition.